Efeito de época-fracionamento e de doses de fertilizante nitrogenado na produção de grãos e em outros caracteres agronômicos do sorgo granífero (Sorghum bicolor (L) Moench) - de Freitas Pereira , José; N Fontes , Luiz Antônio; Domingos Galvão , José; Condé, Alcides R (Revista Ceres, 2025)
During the 1975 and 1976 growing seasons in Viçosa, Minas Gerais, experiments were conducted on the effects of split application of nitrogen fertilizer on grain production and agronomic characteristics of grain sorghum. The soil of the experimental area was a reddish-yellow terrace podzol.